Factors enhancing the performance of SMEs' services sectors: A conceptual framework - Mohd Darus, Norazlina; Yunus, Ahmad Rozelan; Rahman, Noor Watee (Research Gate, 2017)
Small and Medium Enterprises (SMEs) services sector should be competent and capable enough to compete in the international arena. Hence, this conceptual paper is identifying challenges factors that could examine the enhancement of business performance, survival and success. Consequently,SMEs of services sectors’ performance must also shift into the global knowledge-based economy. Therefore, the SMEs’ business success sustainability highly depends on factors such as innovation, quality and intellectual capital. Furthermore, the strong knowledge of new challenges enables them to access the information of recent customer preferences,added values with current technologies. As a result, this study strives to investigate the factors that enhance the performance of SMEs services sector. In the end, this study, it is expected to contribute to new information and data support to the SMEs’ in enhancing their performance in the services sector in central part of Malaysia as well employees, students and researchers. This would be the enabler solution for future challenges.